Relayout Gudang Kayu Menggunakan Metode Shared Storage Location Untuk Mengurangi Jarak Perpindahan Material - Saputra, Satria Ardiansyah; Wati, Putu Eka Dewi Karunia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT ABC is a company operating in the manufacturing sector, specifically in the production of semi-finished processed wood, implementing a make-to-order production system. Currently, the company faces several challenges in warehouse management, where the storage area for finished goods is still mixed with raw materials and production areas. This situation is further exacerbated by the stacking arrangement of materials not meeting standards, resulting in inefficient use of space and difficulties in the retrieval process. This study aims to redesign the layout of PT ABC's warehouse using the Shared Storage Location method. This method is designed to allocate storage space flexibly to more effectively separate raw material and finished goods storage areas. The main focus of this design is to optimize storage capacity and minimize material handling distances.With the implementation of the new layout, it is expected that the company can reduce operational time.